Pengaruh Penggunaan Media Sosial Instagram @Iqomic terhadap Pemenuhan Kebutuhan Informasi Keagamaan Followers Tunarungu - Rizqulloh, Muhammad Raihan; Nur Chidayah, Prita Priantini; Rojudin, Rojudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to determine the extent to which the use of the Instagram social media account @iqomic influences the fulfillment of religious information needs among deaf followers. The theory used is the Uses and Gratifications theory proposed by Herbert Blumer and Elihu Katz in 1974. This research employs a case study method with a quantitative approach. Data analysis results show that the use of the Instagram account @iqomic has a less significant impact on fulfilling the religious information needs of deaf followers. This is due to the higher frequency of text-based image posts compared to video content with subtitles.